Integration of technology in the learning of Al-Islam and Kemuhammadiyahan at Muhammadiyah Elementary School - Alfia Zul Faida; Suyatno Suyatno (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Al-Islam and Kemuhammadiyahan are characteristics of Muhammadiyah-based schools. Al-Islam and Muhammadiyah have cultural and religious values ​​that are expected to be implemented in everyday life. This research aims to 1) Analyze the integration of technology in learning Al-Islam and Muhammadiyahan and 2) Analyze the supporting and inhibiting factors for integrating technology in learning Al-Islam and Muhammadiyah at SD Muhammadiyah Purwodiningratan Yogyakarta. The type of research is qualitative with a case study approach. The research subjects were the school principal, Al-Islam and Muhammadiyah teachers, and students. Data collection techniques use observation, interviews, and documentation. The collected data was analyzed by data collection, data reduction, data presentation, and drawing conclusions. The results show that 1) Technology integration in Al-Islam and Muhammadiyah learning contains 6 stages, namely (a) Integration of learning technology through analysis of student characteristics, (b) Determining learning objectives by integrating technology, (c) Choosing methods, media, and teaching materials by integrating technology, (d) Using media and teaching materials by integrating technology, (e) Student activity in learning integrated with technology, (f) Evaluation and revision of learning integrated with technology and. (2) Supporting and inhibiting factors for technology integration in Al-Islam and Muhammadiyah learning include teacher capacity development training, adequate school facilities to support technology integration, and use of social media. Meanwhile, the inhibiting factors are, time utilization is not optimal, technology maintenance is lacking, and students are less focused when receiving learning so they become lazy in studying.